Pluralisme Pengaturan Umur Kecakapan Dalam Pembebanan Hak Tanggungan - Widana Putra, I Made (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
SKMHT (Power of Attorney to Grant a Mortgage) shall be concluded through a notarial deed or Land Conveyancer’s deed as regulated in Article 15 paragraph (1) of Law No. 4 of 1996. Article 39 paragraph (1) of Law No. 30 of 2004 in conjunction with Law No. 2 of 2014 stipulate that an appearer before a Notary Public shall be minimum eighteen (18) years old. However, to conclude an SKMHT, PPAT (Land Conveyancer) applies the age requirement of minimum twenty-one (21) years old as regulated in the provision of article 330 of BW (Civil Code of the Republic of Indonesia). As such, there are two (2) contradictive age requirements to conclude an SKMHT, namely horizontal norm conflict (geschijld van normen) between Article 330 of BW and Article 39 paragraph (1) of Law No. 30 of 2004 in conjunction with Law No. 2 of 2004. Apart from the two (2) provisions referred to above, Law No. 1 of 1974 also regulates the age requirement, namely article 47 and article 50. The validity of SKMHT will affect the execution of APHT (Deed of Mortgage Granting) and the registration of mortgage granting. Based on the said backgrounds, the main subject of this study is what the age requirement should be in order to able to conclude an SKMHT, APHT and to register a Mortgage Granting. This study constitutes a normative legal study derived from the existing norm conflict between article 330 of BW and article 39 paragraph (1) of Law No. 30 of 2004 in conjunction with Law No. 2 of 2014, and among article 330 of BW and article 47, article 50 and article 66 of Law No. 1 of 1974. Meanwhile, this study adopts the Statue Approach and Analytical & Conceptual Approach. The legal stuff resources come from primary legal stuff resources and secondary legal stuff resources. The methodology to collect legal stuff resources is the snow ball principle, where the resources were inventoried and identified in order to able to analyze the existing problems in this study. The results of this legal study indicate that normatively, an SKMHT shall be concluded by using the age requirement of eighteen (18) years old. However, Notary Public and PPAT in practice remain to adopt the age requirement of twenty-one (21) years old to conclude an SKMHT. PPAT should also apply the age requirement of eighteen (18) years old to conclude APHT. However, PPAT in practice remain to adopt the age requirement of twenty-one (21) years old. Therefore, the process to conclude an APHT will not be able to be carried out if the subject of notarized SKMHT is eighteen (18) years old. The same also applies to the registration of mortgage granting at the Land Office because the Land Office requires the age requirement of twenty-one (21) years old as regulated in the provision of Article 330 of BW. As a consequence, if the subject has not yet reached the minimum age requirement, the mortgage granting cannot be registered.
Keywords: Notary Public, PPAT (Land Conveyancer), SKMHT (Power of Attorney to Grant a Mortgage), APHT (Deed of Mortgage Granting) and Registration of Mortgage Granting